The Regulatory Role of Histone Modification on Gene Expression in the Early Stage of Myocardial Infarction - Wang, Jinyu; Lin, Bowen; Zhang, Yanping; Ni, Le; Hu, Lingjie; Yang, Jian; Xu, Liang; Shi, Dan; Chen, Yi-Han (Frontiers in Cardiovascular Medicine, 2020)
Myocardial infarction (MI) is a fatal heart disease with high morbidity and mortality. Various studies have demonstrated that a series of relatively specific biological events occur within 24 hours of MI. However, the roles of histone modifications in this pathological process are still poorly understood. To investigate the regulation of histone modifications on gene expression in early MI, we performed RNA sequencing (RNA-seq) and chromatin immunoprecipitation sequencing (ChIP-seq) on myocardial tissues 24 hours after the onset of MI. The genome-wide profiles of five histone marks (H3K27ac, H3K9ac, H3K4me3, H3K9me3, and H3K27me3) were explored through ChIP-seq. RNA-seq identified 1032 differentially expressed genes (DEGs) between the MI and sham groups. ChIP-seq analysis found that 195 up-regulated DEGs were modified by change of at least one of the three active histone marks (H3K27ac, H3K9ac, and H3K4me3), and the biological processes and pathways analysis showed that these DEGs were significantly enriched in cardiomyocyte differentiation and development, inflammation, angiogenesis and metabolism. In the transcriptional regulatory network, Ets1, Etv1, and Etv2 were predicted to be involved in gene expression regulation. In addition, by integrating super-enhancers (SEs) with RNA-seq data, 76 DEGs were associated with H3K27ac-enriched SEs in the MI group, and the functions of these SEs associated DEGs were mainly related to angiogenesis. Our results suggest that histone modifications may play important roles in the regulation of gene expression in the early stage of MI, and the early angiogenesis response may be initiated by SEs.